Combining a Data Management System and Case-Based Learning to Address Various Types of Needs in Equine Orthopaedics - Jean-Michel Vandeweerd; John Davies (CRIFPE - Centre de recherche interuniversitaire sur la formation et la profession enseignante, 2006)
This article describes a clinical data collecting system in the field of equine orthopedics, which was implemented and experimented to optimize the use of the entire caseload of The Philip Leverhulme Equine Hospital by generating automatically online learning activities. A Microsoft Access database was designed to collect clinical data and documentation about patients. The scripting language of a website interacts with the database to allow retrieval of data for case presentation, viewing of medical techniques and practice of clinical observations and diagnoses. Selfassessment with mechanized feedback and analysis of performance allow reflective learning.